PENGARUH PENDIDIKAN KESEHATAN MEDIA VIDEO ANIMASI PERTOLONGAN PERTAMA KEGAWATDARURATAN PADA KASUS FRAKTUR TERHADAP PENGETAHUAN SISWA DI SMK - Oscar Ari Wiryansyah; Diana (LPPM STIKes Mitra Adiguna, 2026)
First aid in emergency situations is the initial care provided to victims from the moment they are found until they are transported to a healthcare facility. The accuracy and quality of first aid play a crucial role in determining the victim’s subsequent condition and survival. Providing appropriate first aid for fracture cases requires adequate knowledge and strong self-confidence to ensure safe and effective actions. One effort to improve such knowledge is through health education using animated video media. This study aimed to determine the effect of health education using animated video media on emergency first aid for fracture cases on the knowledge level of students at SMK Telenika Palembang. This study employed a quantitative approach with a pre-experimental design using a one-group pretest–posttest design. The study population consisted of individuals within the SMK Telenika Palembang environment, with a total sample of 51 respondents selected based on inclusion and exclusion criteria. The instruments used were a knowledge questionnaire and animated video media. Data analysis was conducted using univariate and bivariate analysis with the Wilcoxon test. The results showed an increase in respondents’ knowledge before and after the health education intervention. The Wilcoxon test revealed a p-value of 0.000 (p < 0.05), indicating a statistically significant difference. It can be concluded that health education using animated video media has a significant effect on improving students’ knowledge of emergency first aid for fracture cases at SMK Telenika Palembang.